Neuropsychological considerations for long-duration deep spaceflight - Faerman, Afik; Clark, Jonathan B.; Sutton, Jeffrey P. (Frontiers in Physiology, 2023)
The deep-space environment introduces multiple and simultaneous risks for the functioning and health of the central nervous system (CNS), which may impair astronauts’ performance and well-being. As future deep-space missions to Mars, moons, or asteroids will inevitably exceed current low-Earth orbit stay durations and are estimated to require up to 3 years, we review recent evidence with contemporary and historic spaceflight case studies addressing implications for long-duration missions. To highlight the need for specific further investigations, we provide neuropsychological considerations integrating cognitive and motor functions, neuroimaging, neurological biomarkers, behavior changes, and mood and affect to construct a multifactorial profile to explain performance variability, subjective experience, and potential risks. We discuss the importance of adopting a neuropsychological approach to spaceflight missions (i.e., “space neuropsychology”) in future research and draw specific recommendations for future research.